The Effectiveness of Interactive PowerPoint in Teaching Speaking Narrative Text in Senior High School - Susanti, Rosalina; Zamzam, Ahmad; Lail, Husnul (Journal of Linguistics, Literacy, and Pedagogy, 2024)
The aim of this research is to examine whether interactive PowerPoint is effective or not in teaching speaking narrative text. This research used a quantitative approach using a quasi-experimental design. This research was conducted in senior high school, with a sample of two classes determined by cluster random sampling technique consisting of 50 students. There were 25 students in class X-B and 25 students in class X-K. The research instrument is speaking assessment task using extensive (monologue) with the topic “The Legend of Malin Kundang” and “Princess Mandalika”. The students’ performance was measured using analytic rubrics. The result of data analysis using SPSS version 29th. The hypothesis testing results proved that the null hypothesis (Ho) was rejected because the value t–test (2.039) was higher than t-table (2.011). This research shows that interactive PowerPoint is effective in teaching speaking narrative text.